PROBLEMS AND PROSPECTS OF REFORMING STATE CONTROL IN THE RUSSIAN FEDERATION - Anna V. Lipuntsova (Russian Studies in Law and Politics)
The article is devoted to an urgent topic in the context of the ongoing transformation of public administration in Russia – the problems and prospects for the development of state control. The subject of the analysis is the currently available results of changes in control and supervisory activities in connection with the entry into force of new legislative acts in this area. The author aims to conduct a theoretical and legal characterization of the reform of state control. The study analyzes the approaches to the essence of state control that have developed in the scientific literature, considers the most priority areas for the development of control and supervisory activities, and provides analytical data. The author makes proposals to improve the legislation laying the legal foundations for the implementation of state control. The research is based on both general scientific and private scientific methods. The formal legal method is used as a special method. The results of the research can be applied for further theoretical work in the framework of administrative law, as well as in the practical activities of legislative and executive bodies of state power.